Efeitos do exercício resistido sobre componentes do sistema purinérgico e parâmetros de estresse oxidativo em modelo experimental de sepse - Miron, Vanessa Valéria (2018)
Sepsis is a generalized infection that causes changes in the purinergic and immune systems, the inflammatory parameters and the oxidative status of the patients. Physical exercise, through its anti-inflammatory and antioxidant properties, has emerged with a tool to prevent complications and / or worsening of sepsis. In this study, we investigated whether twelve weeks of physical exercise would be able to prevent the changes caused by the induction of sepsis in rats, components of the purinergic system, oxidative stress and inflammatory parameters. For this, male Wistar rats were divided into four groups: control, exercise (EX), lipopolysaccharide (LPS) and EX + LPS. A 1-meter-high ladder was used for the animals to perform twelve weeks of resistance exercise. After 72 hours of the last exercise, the animals received 2.5 mg / kg of LPS for induction of sepsis, and 24 hours later, cardiac puncture and lung, lymphocytes and serum were collected for the analysis. The results showed that exercise was able to prevent, in septic animals: 1) the increase in body temperature; 2) increased lipid peroxidation and reactive species levels in the lung; 3) the increase in serum ATP levels; 4) the changes in the activity of the enzymes ectonucleotidases in lymphocytes, partially; 5) the change in the density of purinergic enzymes and receptors in the lung and, 6) the increase in IL-6 and IL-1β gene expression. The results are expected to elucidate the involvement of purinergic signaling and oxidative stress in the mechanisms by which exercise can prevent changes caused by sepsis. In this way, encourage regular practice of resistance exercise to better prepare the body against sepsis and other diseases related to inflammation.